Investigation of supplement use and knowledge among Japanese elite athletes for the Tokyo 2020 Olympic/Paralympic games and the Beijing 2022 winter Olympic/Paralympic games - Myoenzono, Kanae; Yasuda, Jun; Takai, Eri; Shinagawa, Akiho; Kaneko, Noburo; Yoshizaki, Takahiro; Namma-Motonaga, Keiko; Yoshino, Masae; Kondo, Emi; Nakajima, Kohei; Hangai, Mika; Kamahara, Kazuyuki; et al. (Frontiers in Sports and Active Living, 2023)
Elite athletes frequently invest in the use of supplements to optimize their dietary regimens and enhance their athletic performance. However, unregulated and unplanned use of supplements can lead to adverse consequences, including anti-doping rule violations or health issues. Thus, athletes should verify their diets, consider scientific evidence, and take necessary precautions regarding supplements before use. To date, no study has explored whether athletes check these factors before using supplements. This study aimed to investigate supplement use using a questionnaire administered to 1,392 athletes (including candidate athletes) who participated in the Tokyo 2020 Olympic/Paralympic and Beijing 2022 Winter Olympic/Paralympic Games. Participants were categorized as follows: 1,040 participants in the Tokyo 2020 Olympic Games, 83 in the Tokyo 2020 Paralympic Games, 239 in the Beijing 2022 Winter Olympic Games, and 30 in the Beijing 2022 Winter Paralympic Games. We collected data on supplement use and gained further knowledge through interviews with the athletes. Approximately 70% of Tokyo 2020 Olympic/Paralympic and Beijing 2022 Winter Olympic athletes and approximately 50% of Beijing 2022 Winter Paralympians used supplements. Over 50% of athletes had not received a doctor's diagnosis or a dietitian's evaluation before supplement use. Moreover, only 50% of the athletes who used dietary supplements reviewed the scientific evidence for the dietary supplements before using them and justified their choice based on their own investigation, while those who did not use dietary supplements cited either a lack of need or fear of an anti-doping rule violation. Considering the holistic health and performance of athletes, as well as the risk associated with unregulated use, such as overdose and anti-doping rule violations, there is a need for nutritional education on supplement use for athletes and their entourages.